Unbalanced growth and macromolecular synthesis in Streptococcus mutans FA-1. - Mattingly, S J (1976)
The continued synthesis of deoxyribonucleic acid, protein, cell wall peptidoglycan and intracellular iodophilic polysaccharide (IPS) by Streptococcus mutans strain FA-1 after several treatments intended to inhibit protein synthesis was studied. Exponential-phase cultures were: (i) simultaneously deprived of two required amino acids (cystine and leucine) that are not present in the cell wall peptidoglycan of this species; (ii) depreived of required amino acids (lysine or glutamate plus glutamine ) that are present in both peptidoglycan and protein; or (iii) treated with tetracycline. Each of these three types of treatment was accompanied by a different pattern of unbalanced growth. The patterns of unbalanced growth that accompanied treatments (i) or (ii) differed substantially from the patterns observed previously for Streptococcus faecalis ATCC 9790, a noncariogenic organism that does not contain IPS. In contrast to S. faecalis 9790, S. mutans FA-1 failed to accumulate peptidoglycan and thicken its wall when deprived of non-wall amino acids. Instead, S. mutans FA-1 continued to accumulate IPS to levels substantially higher than those found in exponential-phase cells. Again, in contrast to S. faecalis, S. mutans FA-1 failed to autolyze upon deprivation of essential precursors of wall peptidoglycan. Under conditions of lysine of glutamate/glutamine deprivation, S. mutans FA-1 continued to accumulate IPS to very high levels. Treatment with tetracycline did result in peptidoglycan accumulation and wall thickening in a manner very similar to that observed previously for inhibition of protein synthesis in S. faecalis. Realtively little IPS synthesis continued after tetracycline treatment. Accumulation of IPS appeared to occur when both ribonucleic acid and peptidoglycan synthesis were severely inhibited. The observations are discussed in terms of the survival of cariogenic organisms in the oral environment.